STRUCTURE AND SEMANTICS OF PSYCHLOGICAL PHRASEMES IN ENGLISH (QUANTITATIVE DESCRIPTION) - Bartkov, Boris (Revista Inclusiones, 2020)
The relevance of the problem investigated can be explained by the growing interest in accurate quantitative description of terminology in general and phraseme terms in particular. The article aims (1) to develop quantitative description of the distribution of phraseme terms according to their structural models and semantic classes, namely: fusions, unities, and combinations; (2) to compare quantitatively obtained characteristics with those in another terminology (namely: automobiles) to get a more general perspective on the description of different terminological systems in English. The quantitative method was used as the main one to explore the problem (the author used a formula estimating the comparison coefficient of two systems for several parameters), which enabled to accurately compare both structural and semantic characteristics of phraseme terms in the field of psychology. The result of the study was the first ever estimation of the shares of semantic classes (using the new definitions the author had formulated earlier) which was done for psychological terminology. This made it possible to quantitatively compare them with automobile terms and the literary norm. The author found a quantitative correlation between the structural models of phraseme terms of psychology and carried out their quantitative comparison with the share of models in English automobile terminology.